Clinical and Echocardiographic Outcomes After Bariatric Surgery in Obese Patients With Left Ventricular Systolic Dysfunction. (March 2016) - Vest, Amanda R.; Patel, Parag; Schauer, Philip R.; Satava, Mary Ellen; Cavalcante, João L.; Brethauer, Stacy; Young, James B.
Abstract : Background—: Obesity is a risk factor for development of left ventricular systolic dysfunction (LVSD) and can complicate LVSD management, especially for individuals in whom cardiac transplantation is indicated. Bariatric surgery is increasingly recognized as a safe and effective intervention to achieve marked weight loss, but experience is limited in the LVSD population. Methods and Results—: We retrospectively reviewed patients with obesity and left ventricular ejection fraction (LVEF) <50% who underwent bariatric surgery at a tertiary center 2004 to 2013. An analysis of outcomes and efficacy compared 42 surgical patients with LVSD to 2588 without known LVSD. The LVSD group had greater baseline prevalence of comorbidities and showed a slight excess of early postoperative heart failure and myocardial infarction. However, patients with LVSD achieved good weight loss efficacy (mean decrease 22.6%) and no excess in mortality at 1 year. An overlapping cohort of 38 patients with LVSD had both pre- and postoperative echocardiographic images available for review by 2 blinded readers. Obese nonsurgical controls were matched on age, sex, initial LVEF, and interval between echocardiograms. There was a mean pre- to postoperative LVEF improvement of +5.1% ±8.3 ( P =0.0005) for surgical subjects, but not for controls (+3.4%±10.5, P =0.056). Among surgical subjects, 11 patients had an LVEF improvement of >10%, whereas only 6 improved by >10% among nonsurgical controls. Conclusions—: At experienced centers, bariatric surgery may be a safe and effective intervention for obese patients with LVSD. Bariatric surgery was associated with an improvement in LVEF, although the magnitude of change was on the cusp of clinical significance. Abstract : Supplemental Digital Content is available in the text.